Fecal lipid markers in tandem with ancient sedimentary DNA as a tool for tracing past livestock farming from soils and sediments - Fiedler, Sabine; Scherer, Sascha; Krause-Kyora, Ben (Frontiers in Environmental Archaeology, 2025)
Reconstructing past environments can be challenging when archaeological materials are missing. The study of organic molecules, which remain as traces in the environment over millennia, represents one way to overcome this drawback. Fecal lipid markers (steroids and bile acids) and ancient sedimentary DNA offer a complementary and cross-validating analytical tool to broaden the range of methods used in environmental archaeology. However, little is known about the benefits of combining these two approaches. We present a brief overview of the current state of knowledge on fecal lipid markers and ancient sedimentary DNA. We identify scientific and methodological gaps and suggest their potential relevance for a better understanding of dynamic, human-animal relationships of the past. With this review, we aim to facilitate new research avenues, both in established disciplines and in conjunction with analytical approaches that have rarely been combined to date.